SANAD DAN MATAN HADIS DALAM PERSPEKTIF ORIENTALIS - Latifah Anwar (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Abstract : In the mid-19th century, orientalists began to conduct a lot of research on hadith. They tended to doubt and question the status of traditions in Islam and they even opposed the authenticity of the traditions. Some orientalists considered the hadith as a collection of anecdotes, so its authenticity could not be guaranteed. The orientalists also examined the time that the use of sanad of the Prophet's hadith began. They had different opinions about the beginning of the using of the sanad. Some orientalists stated that the sanad in the books of the hadith were only made by hadith experts in the second or third century of Hijriyah, meanwhile other orientalists stated that the use of sanad in narrating the hadith had been started since the end of the first century of Hijriyah. Most of the hadiths were considered to be false among the orientalists. Some orientalists considered the use of sanad initially as a simple form, and only developed into a perfect sanad in the middle of the 3rd century of Hijriyah. Hadith was considered a product of history, not as a theological belief, even orientalists considered the scholars of hadith experts and scholars of ra'yi to had made hadiths. Criticism of Jewish and Christian orientalist and missionaries towards the hadith greatly influenced Muslims thought. They published writings that were widely publicized, so that they could be read by Muslims. The orientalist thought eventually influenced Muslims thought, so the anti-Hadith movements emerged among Muslims. Keywords: Matan; Orientalist;Sanad